2008
DOI: 10.1007/s10695-008-9239-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of oocyte development in natural habitat and captive Salminus hilarii Valenciennes, 1850 (Teleostei: Characidae)

Abstract: Fecundity and oocyte development in Salminus hilarii female brood stock were analyzed with the aim of investigating the impact of migration impediment on oogenesis. Histological analyses of the ovaries were performed in adult females caught in two different environments--the Tietê River (natural) and captivity--and the gonadossomatic index, oocyte diameter and fecundity determined. Five germ cell development stages (oogonium, perinucleolar, cortical alveoli, vitellogenic, ripe) and two other structures (postov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 24 publications
2
37
0
7
Order By: Relevance
“…Histological analysis showed that the stage of maturation reached is adequate for induced ovulation, due to the presence of several vitellogenic oocytes and post-ovulatory follicles after induction. However, some oocytes were not released and became atretic (Dias et al, 1998(Dias et al, , 2005Honji et al, 2006Honji et al, , 2009. This phase of the development is observed and discussed in some works, including studies in S. hilarii (Takahashi, 2006;Honji et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Histological analysis showed that the stage of maturation reached is adequate for induced ovulation, due to the presence of several vitellogenic oocytes and post-ovulatory follicles after induction. However, some oocytes were not released and became atretic (Dias et al, 1998(Dias et al, , 2005Honji et al, 2006Honji et al, , 2009. This phase of the development is observed and discussed in some works, including studies in S. hilarii (Takahashi, 2006;Honji et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The general morphology of eggs and larvae from G1 and G2 did not differ during development. Therefore, this analysis was performed only to confirm the stage of development because details of this development have already been described by Honji et al (2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations